2021
DOI: 10.3390/cells10092431
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Metabolic and Stress Responses of Human Embryonic Stem Cells to FTH1 Gene Silencing

Abstract: Embryonic stem cells (ESCs) are pluripotent cells with indefinite self-renewal ability and differentiation properties. To function properly and maintain genomic stability, ESCs need to be endowed with an efficient repair system as well as effective redox homeostasis. In this study, we investigated different aspects involved in ESCs’ response to iron accumulation following stable knockdown of the ferritin heavy chain (FTH1) gene, which encodes for a major iron storage protein with ferroxidase activity. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Another study demonstrated that mild oxidative stress provoked by exposure to glucose oxidase enhanced osteogenic differentiation and mineralization in mouse ESCs, which was inhibited by Nrf2 knockdown (Sim et al, 2016 ). It was reported that silencing of FTH1 , which encodes a major iron storage protein, activated NRF2 signaling and induced expression of metabolism-related NRF2 target genes, G6PD and PGD in hESCs (Scaramuzzino et al, 2021 ). Considering NRF2 as a transcription factor that modulates Fth1 and also ferritin light chain ( Ftl ) transcription (Kwak et al, 2001 ; Thimmulappa et al, 2002 ), it could be assumed that the FTH1 -NRF2 axis might contribute to iron homeostasis in hESCs, leading to metabolic changes.…”
Section: Clotho: Cell Birth (Stem Cells)mentioning
confidence: 99%
“…Another study demonstrated that mild oxidative stress provoked by exposure to glucose oxidase enhanced osteogenic differentiation and mineralization in mouse ESCs, which was inhibited by Nrf2 knockdown (Sim et al, 2016 ). It was reported that silencing of FTH1 , which encodes a major iron storage protein, activated NRF2 signaling and induced expression of metabolism-related NRF2 target genes, G6PD and PGD in hESCs (Scaramuzzino et al, 2021 ). Considering NRF2 as a transcription factor that modulates Fth1 and also ferritin light chain ( Ftl ) transcription (Kwak et al, 2001 ; Thimmulappa et al, 2002 ), it could be assumed that the FTH1 -NRF2 axis might contribute to iron homeostasis in hESCs, leading to metabolic changes.…”
Section: Clotho: Cell Birth (Stem Cells)mentioning
confidence: 99%
“…To further explore the details of HSV-1-induced ferroptosis, we focused on the antioxidative genes implicated in negatively regulating ferroptosis, including ferritin heavy chain 1 (FTH1), cystine/glutamate antiporter xCT (SLC7A11), the glutamate-cysteine ligase catalytic subunit (GCLC), the glutamate-cysteine ligase modifier (GCLM), and GPX4. FTH1 is a major component of ferritin, an iron storage protein complex that prevents the iron-mediated production of ROS ( 27 ). SLC7A11 is a key component of the Xc system that ingests extracellular cystine in cells, which is then reduced to cysteine for GSH biosynthesis ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…During autophagy, p62 is degraded, leading to the downregulation of NRF2 expression and decreased antioxidant levels in cells [ 66 ]. The decrease in cellular antioxidant levels leads to increased NCOA4 expression levels, which promote the degradation of FTH1 and the expression of DMT1 [ 67 , 68 ]. The degradation of FTH1 leads to iron release, while DMT1 increases iron absorption, leading to iron overload in cells [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%